Pattern of Internal Neck Injuries in Strangulation Deaths With special reference to Laryngeal Fractures - Rayamane, Anand P; M V, Pradeepkumar; Patra, Ambikaprasad; H T, Thejaswi; Katte, S M; Tareeb, Syed (Journal of Indian Academy of Forensic Medicine, 2015)
One of the important finding in strangulation death is injury to laryngeal appendages. A cross  sectional study was done to know the incidence of injury to laryngeal cartilages in strangulation deaths  autopsied at our department from year 2010 to 2012.  A total of 31 cases studied in which ligature strangulation accounted for 18 cases (12 male, 06  female) and manual strangulation 13 cases (7 male and 6 female). Fractures of the hyoid and/or thyroid  cartilage were present in 23 cases. Out of 23 cases, hyoid bone fractures noted in 9 cases (23%) and  thyroid cartilage fractures found in 17 cases (54%). In ligature strangulation cases hyoid bone fracture  present in 5 cases (28%) and thyroid cartilage fracture present in 9 cases (50%). In manual strangulation  cases hyoid bone fracture noted in 4 cases (31%) and thyroid cartilage fracture were seen in 8 cases  (62%). Cricoid cartilage fracture was not found in our study. Among external features sub-conjunctival  hemorrhage was seen in 19 cases and nasal bleeding in 10 cases. Hemorrhage in strap muscles seen in  all cases. Thyroid cartilage fracture is more common than hyoid bone fracture in both Ligature and  Manual strangulation deaths.
Keywords: Strangulation; Laryngeal fractures; Hyoid and thyroid cartilage